My Tongue is a Mountain: Land, Belonging and the Politics of Voice - Sandra Yellowhorse (Genealogy, 2020)
Indigenous story is about place and our orientation to the place(s) we live through and in. This essay is about Diné (Navajo) identity and its entanglements with the authority of words and the politics of voice within the academy. It is about how voice or narrative are political acts that ground Indigenous peoples in land and territory. In Diné communities, there are ongoing discussions regarding the politics of authority and representation in the erasure of Indigenous voices in academic spaces. Such academic erasure has ripple effects into the ongoing contestation of land and belonging. These ripple effects fuel identity politics among Diné people on the community level. I argue that Diné people themselves are erased and the everyday narrations of our realities and experiences through these normalized academic processes. In addressing those academic processes, I draw attention to another framework for identity politics that encourages and supports not only our voices as Diné people but upholds our intellectual sovereignty and claims to land. I engage narrative to bring forward an understanding that our relationships to words and story extend beyond our tongues.